Community schools in action : lessons from a decade of practice - Dryfoos, Joy G.; Quinn, Jane, M.S.W; Barkin, Carol (OUP E-Books., 2005)
A community school differs from other public schools in important ways: it is generally open most of the time, governed by a partnership between the school system and a community agency, and offers a broad array of health and social services. It often has an extended day before and after school, features parent involvement programs, and works for community enrichment. How should such a school be structured? How can its success be measured? "Community Schools in Action: Lessons from a Decade of Practice" presents the Children's Aid Society's (CAS) approach to creating community schools for the 21st century. CAS began this work more than a decade ago and today operates thirteen such schools in three low-income areas of New York City. Through a technical assistance center operated by CAS, hundreds of other schools across the country and the world are adapting this model. Based on their own experiences working with community schools, the contributors to the volume supply invaluable information about the selected program components.; They describe how and why CAS started its community school initiative and explain how CAS community schools are organized, integrated with the school system, sustained, and evaluated. The book also includes several contributions from experts outside of CAS: a city superintendent, an architect, and the director of the Coalition for Community Schools. Co-editors Joy Dryfoos, an authority on community schools, and Jane Quinn, CAS's Assistant Executive Director of Community Schools, have teamed up with freelance writer Carol Barkin to provide commentary linking the various components together. For those interested in transforming their schools into effective child and family-centered institutions, this book provides a detailed road map. For those concerned with educational and social policy, the book offers a unique example of research-based action that has significant implications for our society